Insulin resistance increases as days on feed advance in feedlot Bos indicus beef cattle offered a high-concentrate finishing diet - Sousa, Osvaldo A. de [UNESP]; Cappellozza, Bruno I.; Fonseca, Vitor G L; Cooke, Reinaldo F. (Oxford University Press (OUP), 2022)
This experiment evaluated the effects of advancing days on feed (DOF) on insulin resistance (IR) of finishing Bos indicus bulls offered a high-concentrate diet. On day 0, 100 Bos indicus Nellore bulls were housed in 12 feedlot pens (8 or 9 bulls/pen) for a 108-d feeding period, in a manner that all pens had an equivalent BW at the beginning of the finishing period. Bulls received the same diets throughout the 108-d feeding period. Diets were corn-based (38% starch) and were offered in amounts to ensure ad libitum intake. Individual shrunk BW was obtained on days 0 and 108 after 16 h of feed and water withdrawal, whereas unshrunk BW was recorded on days 19 and 60 for average daily gain (ADG) calculation. From days 0 to 108, feed intake and feed efficiency (FE) were calculated from each pen. Blood samples were collected on days 0, 60, and 108 to assess serum concentrations of haptoglobin, cortisol, glucose, and non-esterified fatty acids (NEFA), and insulin. Glucose, NEFA, and insulin concentrations were used to determine revised quantitative insulin sensitivity check index (RQUICKI), so that lower RQUICKI values indicate a greater IR of the herd. Pen was used as the experimental unit. Overall, DMI increased as DOF also increased (R2 = 0.71), being greater from days 19 to 60 and 60 to 108 vs. 0 to 19 (P < 0.0001), but did not differ between days 19 to 60 and 60 to 108 (P = 0.79). Conversely, ADG and FE linearly decreased as DOF increased from days 0 to 108 (P < 0.0001; R2 = 0.68 and 0.79, respectively). Log-transformed RQUICKI decreased as DOF increased up to 108 (P < 0.0001; r = -0.61). Similarly, serum concentrations of haptoglobin and cortisol increased as RQUICKI increased (P < 0.0001; r = 0.43 and 0.67, respectively). In summary, insulin resistance, per RQUICKI, increased and performance reduced in feedlot bulls with the advance of days on feed. Moreover, inflammatory markers were also positively associated with insulin resistance, suggesting that inflammation might be involved with the incidence of insulin resistance.

This experiment was designed to evaluate the effects of feeding a high-starch during the feedlot phase (108 d) on performance, inflammatory markers, and insulin resistance of Bos indicus bulls. As feeding period increased, performance of the animals was reduced, whereas inflammatory markers were positively correlated with days on feed. Moreover, insulin resistance state also worsened as days on feeding increased, indicating that offering a high-starch diet for an extended period of time might lead to chronic inflammation and the occurrence of insulin resistance, which, in turn, could help us to explain the often observed decrease on performance of animals in the later stages of the feedlot phase.
Keywords: beef cattle; feedlot; inflammation; insulin resistance; performance